Factors influencing the adaptive re-use of buildings - Bullen, Peter; Love, Peter (Emerald Group Publishing Limited, 2011)
Purpose – Adaptive re-use enables a building to suit new conditions. It is a process that reaps the benefit of the embodied energy and quality of the original building in a sustainable manner. Initiatives to improve the sustainability of buildings have tended to focus on new construction projects rather than existing ones. One reason is the tendency to regard old buildings as products with a limited useful life that have to be eventually discarded and demolished. Much of the existing building stock will still be in use for another 100 years. Thus, there is a need to develop policy and strategies that encourage adaptive re-use and the ongoing sustainability of building stock. The purpose of this paper is to provide a comprehensive review of the factors influencing the decision to adopt an adaptive re-use strategy. Design/methodology/approach – Adaptive re-use is beginning to receive attention, yet there is a lack of consensus as to whether it is an appropriate strategy for meeting the changing needs and demands of developers, occupiers and owners for existing building stock. Considering the limited published research on adaptive re-use in buildings, particularly in the context of sustainability, a comprehensive review of the normative literature is undertaken to determine the factors influencing the decision-making process for its use.Findings – It is revealed that the major drivers for adaptive focus on lifecycle issues, changing perceptions of buildings, and governmental incentives. The barriers to re-use, on the other hand, include a perception of increased maintenance costs, building regulations, inertia of development criteria and the inherent risk and uncertainty associated with older building stock. The identification of drivers and barriers has enabled a balanced view of the adaptive re-use debate to be presented. Research limitations/implications – The paper concludes that more empirical research is required to examine the role of adaptive re-use in the context of its contribution to sustainability if it is to become an effective strategy that drives the formulation of public policy for addressing the issues associated with existing building stock. Practical implications – The research identifies key adaptive re-use issues that need to be addressed by policy makers, developers and owners during the formative stages of the design process so that efforts toward sustainability can be ameliorated. Addressing a building's adaptive re-use will significantly reduce whole life costs, waste and lead to the improved building functionality. Originality/value – This paper provides policy makers and key decision makers with the underlying factors that need to be considered when implementing an adaptive re-use policy as part of their sustainability strategy.